Research on the Training Mode of College Students' Innovation and Entrepreneurship Talents under the Background of Industry-Education Integration (Journal of economic and management development research, 2026)
Against the backdrop of economic restructuring and the continuous advancement of innovation-driven development, society has increasingly higher requirements for high-quality talents with innovative awareness and strong practical abilities. Industry-education integration is one of the essential conditions for connecting the higher education chain and talent training chain with the production, service chain and innovation value creation chain in the industrial system, and it plays a vital role in promoting innovation and entrepreneurship education in colleges and universities. At present, the cultivation of innovative and entrepreneurial talents in colleges and universities is still confronted with such problems as insufficient depth of industry-education integration, curriculum system failing to keep pace with the times, low overall competence of teaching staff, and excessively one-sided evaluation methods. Based on the theory of industry-education integration, this paper analyzes the current situation and problems existing in the cultivation of innovative and entrepreneurial talents in colleges and universities. On this basis, it proposes a four-in-one education mechanism featuring synchronized objectives, shared courses, joint practice promotion, and shared evaluation, and puts forward specific measures in terms of policy support, platform construction, faculty enhancement, and campus culture cultivation. The research aims to provide certain theoretical support and reference for colleges and universities to improve the quality of innovation and entrepreneurship education and boost local economic development.
Keywords: Industry-education integration; Innovation and entrepreneurship education; Talent training mode; College education; Practical education